Understanding Speech in Interactive Narratives with Crowdsourced Data - Orkin, Jeff; Roy, Deb (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2012)
Speech recognition failures and limited vocabulary coverage pose challenges for speech interaction with characters in games. We describe an end-to-end system for automating characters from a large corpus of recorded human game logs, and demonstrate that inferring utterance meaning through a combination of plan recognition and surface text similarity compensates for recognition and understanding failures significantly better than relying on surface similarity alone.